Constructing an Isogenic 3D Human Nephrogenic Progenitor Cell Model Composed of Endothelial, Mesenchymal, and SIX2-Positive Renal Progenitor Cells - Lisa Nguyen; Lucas-Sebastian Spitzhorn; James Adjaye (Stem Cells International)
Urine has become the source of choice for noninvasive renal epithelial cells and renal stem cells which can be used for generating induced pluripotent stem cells. The aim of this study was to generate a 3D nephrogenic progenitor cell model composed of three distinct cell types—urine-derived SIX2-positive renal progenitor cells, iPSC-derived mesenchymal stem cells, and iPSC-derived endothelial cells originating from the same individual. Characterization of the generated mesenchymal stem cells revealed plastic adherent growth and a trilineage differentiation potential to adipocytes, chondrocytes, and osteoblasts. Furthermore, these cells express the typical MSC markers CD73, CD90, and CD105. The induced endothelial cells express the endothelial cell surface marker CD31. Upon combination of urine-derived renal progenitor cells, induced mesenchymal stem cells, and induced endothelial cells at a set ratio, the cells self-condensed into three-dimensional nephrogenic progenitor cells which we refer to as 3D-NPCs. Immunofluorescence-based stainings of sectioned 3D-NPCs revealed cells expressing the renal progenitor cell markers (SIX2 and PAX8), podocyte markers (Nephrin and Podocin), the endothelial marker (CD31), and mesenchymal markers (Vimentin and PDGFR-β). These 3D-NPCs share kidney progenitor characteristics and thus the potential to differentiate into podocytes and proximal and distal tubules. As urine-derived renal progenitor cells can be easily obtained from cells shed into urine, the generation of 3D-NPCs directly from renal progenitor cells instead of pluripotent stem cells or kidney biopsies holds a great potential for the use in nephrotoxicity tests, drug screening, modelling nephrogenesis and diseases.